2008
DOI: 10.1016/j.yhbeh.2007.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multiparity on recognition memory, monoaminergic neurotransmitters, and brain-derived neurotrophic factor (BDNF)

Abstract: Recognition memory and anxiety were examined in nulliparous (NP: 0 litters) and multiparous (MP: 5-6 litters) middle-aged female rats (12 months old) to assess possible enduring effects of multiparity at least 3 months after last litter was weaned. MP females performed significantly better than NP females on the non-spatial memory task, object recognition, and the spatial memory task, object placement. Anxiety as measured on the elevated plus maze did not differ between groups. Monoaminergic activity and level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 83 publications
(108 reference statements)
8
58
0
3
Order By: Relevance
“…Dams having had at least one litter typically outperform virgins on tasks of cognitive performance (Kinsley et al 1999, Love et al 2005, Bodensteiner et al 2006, Pawluski et al 2006a, Macbeth et al 2008. Primiparous or multiparous dams are found to have a greater spinal density on hippocampal dendrites compared with nulliparous dams (Pawluski & Galea 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dams having had at least one litter typically outperform virgins on tasks of cognitive performance (Kinsley et al 1999, Love et al 2005, Bodensteiner et al 2006, Pawluski et al 2006a, Macbeth et al 2008. Primiparous or multiparous dams are found to have a greater spinal density on hippocampal dendrites compared with nulliparous dams (Pawluski & Galea 2006).…”
Section: Discussionmentioning
confidence: 99%
“…3a,5a-THP is one such steroidogenic factor that is enhanced throughout pregnancy and has demonstrated neuroprotective and neuroproliferative effects , Djebaili et al 2005, Wang et al 2005, VanLandingham et al 2006, Leonelli et al 2007, Wang et al 2008. Of note, parity has been associated with reductions in age-related cognitive decrement and markers of neurodegeneration, as well as the increased expression of brain-derived neurotrophic factor (Gatewood et al 2005, Pawluski & Galea 2007, Macbeth et al 2008. Whether 3a,5a-THP may underlie some of the cognitive and/or trophic effects associated with reproductive experience has not been systematically investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic high Table 1 Summary of pregnancy and reproduction effects on anxiety, cognition, and neural function in the rodent mother. Windle et al (1997), Shanks et al (1999) # neural activity in regions associated with stress/anxiety da Costa et al (1996), Wartella et al (2003) # in anxiety-related behaviors Lonstein (2005), Pereira et al (2005) After weaning # in anxiety-related behaviors Love et al (2005), Agrati et al, 2008 " in anxiety-related behaviors Byrnes and Bridges (2006), Byrnes et al (2007), Macbeth et al (2008a) Cognition/memory Pregnancy " spatial memory in various stages of pregnancy Galea et al (2000), Bodensteiner et al (2006), Pawluski et al (2006b), Macbeth et al (2008b) Postpartum/ lactation # spatial memory from postnatal day 1-4; Darnaudery et al (2007) " spatial memory by postnatal day 14 After weaning " spatial memory in primiparous and multiparuos females Kinsley et al (1999), Lambert et al (2005), Pawluski et al (2006a), Paris and Frye (2008) " spatial memory in multiparous females months after weaning Gatewood et al (2005), Love et al (2005), Lemaire et al (2006), Macbeth et al (2008a) Neural function Pregnancy " dendritic spines in CA1 hippocampus " neurogenesis in subventricular zone Shingo et al (2003), Furuta and Bridges (2005) " monoamine activity in CA1 and CA3 hippocampus Macbeth et al (2008b) Postpartum/ lactation " dendritic spines in CA1 hippocampus # neurogenesis in DG in early postpartum; returns to normal within 2 weeks postpartum Darnaudery et al (2007), Leuner et al (2007) After weaning…”
Section: Anxiety In the Mothermentioning
confidence: 99%
“…No difference in CA1 dendrites between multiparous and nulliparous females Brusco et al (2008) # dendritic spines in CA1 hippocampus of primiparous females; Pawluski and Galea (2006) " dendritic spines in multiparous females # neurogenesis in DG in primiparous and multiparous females; Pawluski and Galea (2007a,b) " in multiparous compared with primiparous females " LTP in CA1 of multiparous females Tomizawa et al (2003) " excitatory postsynaptic potentiation in primiparous females Lemaire et al (2006) " monoamine activity in OB of multiparous females; no changes in hippocampus Macbeth et al (2008a) All changes are in reference to virgin/nulliparous females, unless otherwise noted. DG: dentate gyrus.…”
Section: Anxiety In the Mothermentioning
confidence: 99%
“…To investigate this, age-matched rats with different breeding histories (no, one, or multiple past pregnancies) are compared. We, and others, have demonstrated that middle-aged rats that have experienced past pregnancies have improved performance in the object recognition task compared to those that have not experienced such breeding history (Macbeth et al 2008;Paris & Frye, 2008). Second, of interest is whether older subjects, with reductions in natural variations in steroids, can respond to hormone replacement.…”
Section: Cognitive Performance Across the Lifespan-role Of Hormonesmentioning
confidence: 99%